(untitled) (European Journal of Marketing and Economics, 2023)
Employee motivation is a key driver of organizational performance and employee retention. An increasing shortage of skilled workers forces companies to think of ways to motivate and retain their employees. Herzberg’s two-factor theory of motivation provides an insight which factors are relevant for motivating employees. The theory founded on research carried out in the 1960’s. Since then, the practical and theoretical tenet of supervision and management has shifted to a different leadership approach. Additive the economic environment is found to be more volatile, unpredictable, complex and ambiguity. VUCA has made its way into organizational science resulting in a focus on agile working methodologies. To add up a generation of millennials demanding for feedback, open communication and team-based workplaces starts to integrate into labour market. Does Herzberg’s theory persist in this new economic environment? Can it be adapted or is a completely new approach inevitable? This organizational psychology related study is aimed to test Herzberg’s theory in a contemporary environment by applying the theory of personal constructs as an investigative method. 61 qualitative repertory grid structured interviews elicited n = 782 personal constructs to investigate the theory. The personal constructs are clustered and compared to the theory of Herzberg.